Arsénico. Del agua a los alimentos - Pérez Carrera, Alejo Leopoldo (2015)
Defined as the king of poisons or "poison of kings", arsenic (As) is one of the most widely distributed elements in the environment. Its origin is associated with different geological environments or human activities. In Argentina, different studies have reported elevated levels of As in groundwater and surface water in different regions. These water sources are important for human and animal consumption. At present As has been recognized as one of the most toxic elements, specially through chronic exposure from drinking water or food. The presence of As in food can be a major source of exposure for humans, even greater than drinking water. The concentration of As in food is variable, in different foodstuffs As content range between 0.1 and 0.9 μg/g. Total As consumption depends on its concentration in food and the percentage it represents in the diet. In this article we summarize the main results of studies conducted to assess the impact of arsenic in water on food qualit.